The Rise of the Dutch Republic $1 (BVolume 07: 1561-62s - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 07: 1561-62" by John Lothrop Motley is a historical account written during the mid-19th century. This volume is part of a larger work that chronicles the events leading up to the Dutch revolt against Spanish rule, focusing specifically on the oppressive role of the Inquisition and the societal reaction to it in the Netherlands during the early 1560s. At the start of this volume, the narrative delves into the causes of the revolt, particularly highlighting the brutalities of the Inquisition that had taken root under the reign of King Philip II of Spain. The chapter describes the various forms of Inquisition present, detailing the relentless persecution faced by those accused of heresy. Notably, it provides harrowing examples of individuals subjected to torture and executions, illustrating the widespread fear and hatred of the regime. The opening sets the stage for the escalating tensions between the populace and the authorities, as figures such as Granvelle emerge as key antagonists in the growing conflict that would ultimately lead to the quest for Dutch independence. (This is an automatically generated summary.)s
Release date is 2004-01-01
This etext was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history